The Comparison of coherence in the ode of "Jikour" by Sayab and "Along the river “by Nima - mohammadhassan amraee (مطالعات زبانی و بلاغی)
The conditions of social, cultural, political, and literary life of Nima and BadrShakirSyab in many cases are similar .Among these, we can refer to a life in rural environments with barbaric nature, social commitments, the influence of Western literary schools, life under the shadow of dictatorship, political tendencies, the use of common literary themes, the pioneering and breaking the tradition in new poetry Which has often attracted the attention of comparative literature experts. The "Jikour and the Trees of the City" ode is one of the most important ode of Seyyeb and, in his own words, is "Jokur of his Poetry". The ode of "along the river" is also an important piece of Nima which have been written in almost the same cultural and social conditions. Observing the similarities and the small volume of the odes, the quality of the coherence in these two odes can be questioned.  The purpose of this paper is to evaluate the coherence and coordination, coherence in the text of the ode "Jikour and trees in the city" of Sayab, Iraqi modernist poet and the "river" of Nima, the Persian modernist poet NimaUshij Which is chosen selectively And written on the basis of descriptive-analytical and statistical methods. The author intends to find the coherence and it factors in poetry of two poets in a comparative analysis and critique with a spectacular and textual looking and with the trust of the systematic theory of Holliday and Hasan, 1985. It can be said that the co-ordination theory of coherence can be used in Persian and Arabic languages, and this pattern can be used in literary and non-literary texts and even quantitatively determine the coherence of the text. The study and application of the theory of coherence of Holliday and Hassan (1985) in the poem of Nima and Sayab showed that The Nima verse (93.65%), because of the greater interaction between the elements of the coherence of the lexical section and its syntax, is more coherent than the Sayab (88.95%). Both poets have succeeded to create an unbreakable link between words and meanings and thus reflect their thoughts and inner desires in the lyrics by using the elements of verbal and grammatical cohesion.